1996
DOI: 10.1088/0029-5515/36/11/i04
|View full text |Cite
|
Sign up to set email alerts
|

High density operation on Frascati Tokamak Upgrade

Abstract: Plasma behaviour in the high density regime has been investigated on the Frascati Tokamak Upgrade (FTU). The items particularly addressed are density limit, MARFE characteristics and fuelling efficiency. With gas puffing, a maximum line average density of 3.2 x 10" m-3 has been obtained in the ohmic regime at q = 5.1, corresponding to 1.7 times the Greenwald limit; while with pellet injection, a value of 3.7 x 10' ' m-' has been reached at Q = 3.5. The density limit appears to be connected with the impurity co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…Machines as diverse as Alcator-C, C-Mod, Doublet III, DITE, and TFTR found MARFE thresholds in the range 0.4 -0.55 n G [66]. FTU has found that MARFEs form at a variable fraction of the density limit with dependences on input power, Z EFF and limiter material [39]. Experiments with beryllium first wall materials in JET found a MARFE formation density which scaled as P IN 0.5 [37].…”
Section: Marfesmentioning
confidence: 99%
See 2 more Smart Citations
“…Machines as diverse as Alcator-C, C-Mod, Doublet III, DITE, and TFTR found MARFE thresholds in the range 0.4 -0.55 n G [66]. FTU has found that MARFEs form at a variable fraction of the density limit with dependences on input power, Z EFF and limiter material [39]. Experiments with beryllium first wall materials in JET found a MARFE formation density which scaled as P IN 0.5 [37].…”
Section: Marfesmentioning
confidence: 99%
“…The Greenwald limit was derived from a relatively small set of data, but predicted the density limits (at least for discharges with flat profiles) for a wide range of devices that were subsequently commisioned including FTU [127,39], JET [57,40], DIII-D [72], TFTR [128], TUMAN-3 [11], TEXTOR [53,48], C-Mod [54], START [129,130], JT60-U [38], TCV [12], ASDEX-Upgrade [41], NSTX [15], MAST [27]. The last devices, large spherical tokamaks with aspect ration R/a < 1.8, may have a density limit 20-40% higher than n G , reasonably good agreement given that the scaling law was derived for machines with a narrow range (3-5) of aspect ratios.…”
Section: Global Scalingmentioning
confidence: 99%
See 1 more Smart Citation
“…The critical conditions for the occurrence of a MARFE may be correlated to the edge plasma parameters, because it is a localized instability within the edge region. It was evidence that the critical value of n e (0.7a)Z e f f in the MARFE onset always correlated with the total input power which has been observed in the FTU [12] and the HT-7 limiter tokamak [7][8], here n e (0.7a) is the line average density, measured at the outermost interferometer channel at r =20 cm (r =0.7a, the minor radius a = 27∼28 cm). In the TEXTOR-94, dependence of the edge electron density (r = a + 1 cm) on the heating power was also observed [13].…”
Section: Introductionmentioning
confidence: 93%
“…In the TEX-TOR tokamak the MARFE generally leads to a disruption. In the FTU tokamak the onset of a MARFE always occurs before achieving the density limit [12]. The critical density for its onset is not a constant for the same magnetic field and plasma current, but depends on the vacuum vessel conditioning procedure and on the material used for the limiter surface [17].…”
Section: Introductionmentioning
confidence: 99%